Bureaucracy, class, and ideology : the Vancouver Trades and Labour Council, 1889-1909 - Leier, James Mark (1991)
Thesis (Ph.D.)-- Memorial University of Newfoundland, 1992. History Bibliography: [411]-429 leaves. This dissertation is an examination of bureaucracy, class, and ideology in the labour movement. It seeks to understand what is meant by the term labour bureaucracy and to determine the degree to which bureaucracy shaped ideology in the Vancouver Trades and Labour Council from 1889 to 1909. -- The first section is an analysis of the theoretical literature and historiography of the labour bureaucracy. As well as providing an overview of the topic, the thesis tries to formulate a different definition of the labour bureaucracy, one that focuses on the power of the bureaucrats, rather than their ideology. The second section is a study of the officials and leaders that made up the VTLC from its beginning in 1889 to the founding of the B.C. Federation of Labour twenty years later. In this section, the ideology of the council is examined to evaluate the impact of bureaucracy on the labour movement. The policies and structure of the council are studied in detail to show how the separation of the leaders from the led developed over time and to demonstrate why bureaucratic solutions -- the hiring of experts, reliance on government intervention, the routinization of procedures, and the creation of labour institutions - were taken and to outline the effect they had. The conflict between labourists and socialists is examined closely to suggest first that bureaucracy is not limited to labour leaders of any single ideology, and second, that the needs of the labour movement and the demands of bureaucracy itself tended to soften ideological battles. Even with the ascension of socialists to the council in 1907-1909, continuity remained the hallmark of the labour council, in part because socialists had no particular commitment to rank-and-file control of the labour movement. Finally, the lives and class positions of the labour leaders are illustrated to try to shed some light on the ways in which bureaucracy, class, and ideology become intertwined.